Pengujian Fungsional Sistem Rental Mobil Berbasis Web Menggunakan Metode Black Box Testing - Dina Nabil Ayyasy; Apriade Voutama (Journal of Students‘ Research in Computer Science, 2026)
The development of web technology has supported digital transformation in various service sectors, including vehicle rental services. A web based car rental system was developed to simplify the process of vehicle booking, data management, and transaction handling. To ensure that the system functioned properly and met user requirements, software testing was conducted using the black box testing method. This testing method evaluated the system functionality by examining the outputs generated from user inputs without analyzing the internal structure of the program code. The testing process covered several main features of the system, including user registration, login authentication, vehicle booking, payment confirmation, and administrative data management. The results showed that all tested operated according to the expected outcomes. The system successfully processed valid input and provided appropriate responses to invalid or incomplete input. These findings indicated that the web based car rental system functioned properly and was able to support vehicle rental services effectively.